Bibliografía sobre: Lógicas no clásicas. Fundamentación, aplicaciones y permanencia. - Jasso Méndez, Jesús; Conforti, Claudio M.; Alonso González, Enrique (Andamios)
The article presents a bibliographic selection on non-classical logics, which have proliferated in the last 60 years. These logics include logical systems such as non-monotonic logics, free logics, and intuitionistic logics. The article is divided into three inquiry sets: foundation, applications, and permanence, and offers a representative selection of theoretical production in this field. Various authors and relevant works in the field of non-classical logic are mentioned, addressing topics such as second-order logic, temporal logic, and abduction logic, among others. Applications of logic in social sciences and computational decision-making are also mentioned.